Rural community learning network traits model - Abu, Roziya; Rafie, Siti Khadijah; Mohamad Tanuri, Zati Atiqah; Ahmad, Mohamad Nadzri (Universiti Teknologi MARA, Kedah, 2017)
Rural Community Learning Network is proposed as a type of learning network approach using and based on local resources, material and knowledge, for instance, using local industries through partnership programs, local associations through affiliation activities, and government and non-government organizations through collaboration events and campaigns. The focus should be on local people supporting local people. The rural public library support in relation to the RCLN would be in the form of providing the physical location and setting, providing and assisting with material and resource needs, and most importantly, organizing the establishment of the network. In the Malaysian context, the Malaysian government, NLM, state libraries, librarians and library assistants are involved directly in providing rural public library services, programs and activities to their local rural communities. There are four traits of Rural Community Learning Network which consist participation, selfhelp and determination, decision-making and leadership.